Biosensor Technologies for Early Detection and Quantification of Plant Pathogens - Dyussembayev, Kazbek; Sambasivam, Prabhakaran; Bar, Ido; Brownlie, Jeremy C.; Shiddiky, Muhammad J. A.; Ford, Rebecca (Frontiers in Chemistry, 2021)
Plant pathogens are a major reason for reduced crop productivity and may lead to shortage of food for both human and animal consumption. Although chemical control remains the main method to reduce foliar fungal disease incidence, frequent use can lead to loss of susceptibility in the fungal population. Also, over-spraying can cause environmental contamination and poses a heavy financial burden on growers. To prevent or control disease epidemics, it is important for growers to be able to detect the causal pathogen accurately, sensitively, and rapidly in order to choose and enact best practice disease management strategies. Several culture-dependent, biochemical, and molecular methods have been developed for plant pathogen detection. However, these suffer from lack of accuracy, specificity, reliability, and rapidity, and they are generally not suitable for in-situ analysis. Accordingly, there is strong interest in developing biosensing systems for early and accurate pathogen detection. There is also great scope to translate innovative nanoparticle-based biosensor approaches developed initially for human disease diagnostics for early detection of plant disease-causing pathogens. In this review, we compare conventional methods used in plant disease diagnostics with new biosensor technologies that may be applied for plant pathogen detection and management. In addition, we discuss challenges facing biosensors and new capability the technology provides to informing disease management strategies.